Taxonomic attribution of the haplic gleysols of the Azerbaijan Republic in world reference base for soil resources - Maharram, Sultan Huseynova; Ismayil, Amin Ismayilov; Pirverdi, Maharram Babayev; Musa, Ali Jafarov (Institute of Advanced Engineering and Science, 2024)
The aim of the research was to obtain new information about the genesis, status, diagnostic features, and properties of the meadow-boggy soils of the Azerbaijan Republic and to perform the taxonomic attribution of those soils in accordance with the international soil classification system in compliance with the world reference base (WRB) for soil resources. Field experiments, physical, and chemical analyses of soil samples were carried out by standard methods. The morphological properties of the meadow-boggy soils in the Greater Caucasus and Lankaran regions of Azerbaijan have been characterized. Carbonate sediments are almost always invisible in the upper layers (13.27-17.14% (No 426); 10.46-27.39% (No 5); 0.87-1.33% (No 55)). According to the humus content, they are not highly humic (1.44-1.85% (No 426); 0.90-1.58% (No 5); 3.10-3.29% (No 55) in the upper layers). The magnitude of the reaction of the soil solution varies from 8.0 to 8.5. For the first time, an attempt is made to determine the name of meadow-boggy soils in accordance with the international soil classification in compliance with the WRB 2015. The above soils are assigned to the gleysols reference soil group (RSG) with various principal and supplementary qualifiers.